Therapeutic Potential of Natural Killer Cells in Gastric Cancer - Du, Yu; Wei, Yongchang (Frontiers in Immunology, 2019)
Gastric cancer (GC) is one of the most common cancer with high incidence rate of cancer death. Despite various therapeutic approaches, the cures and prognosis of advanced gastric cancer remain poor. Natural killer (NK) cells, which are known as important lymphocytes in innate immunity, play vital roles in suppressing GC initiation, progression and metastases. A wide range of clinical settings show increasing the number of NK cells or improving NK cell anti-tumor activity which is promising to GC patients. NK cell adoptive therapy (especially expanded NK cells) is a safe and well-tolerated method, which can enhance NK cell cytotoxicity against GC. Meanwhile, cytokines, immunomodulatory drugs, immune checkpoint blockades, antibodies, vaccines and gene therapy have been found to directly or indirectly activate NK cells to improve their killing activity towards GC. In this review, we summarize recent advancements in the relationship between NK cells and GC, and point out all the innovative strategies that can enhance NK cells function to inhibit the growth of GC.